2006
DOI: 10.1183/09031936.06.00038806
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung diseases associated with amyopathic dermatomyositis

Abstract: The aim of the present study was to clarify the clinical characteristics and prognosis of patients with interstitial lung disease (ILD) associated with amyopathic dermatomyositis (ILD-ADM).The study consisted of 14 consecutive patients with ILD-ADM. Patients were classified into two categories, acute/subacute and chronic forms, according to the clinical presentation of ILD. The clinical features, responsiveness to therapy, and prognosis between the two forms were compared.Nine ILD-ADM patients were categorised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 28 publications
(64 reference statements)
1
116
0
3
Order By: Relevance
“…The limitations of the study by SUDA et al [36] include its retrospective design and small size. Although most patients had a clinical and radiological pattern that differs from IPF, only a minority underwent a lung biopsy (mostly due to the rapid onset of the lung disease).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of the study by SUDA et al [36] include its retrospective design and small size. Although most patients had a clinical and radiological pattern that differs from IPF, only a minority underwent a lung biopsy (mostly due to the rapid onset of the lung disease).…”
mentioning
confidence: 99%
“…In this regard, in the current issue of the European Respiratory Journal, SUDA et al [36] have addressed novel aspects of the clinical presentation of ILD in dermatomyositis. Hence, in a retrospective cohort of 14 patients with amyopathic dermatomyositis, they identified two distinct profiles according to the clinical onset.…”
mentioning
confidence: 99%
“…However, CD4/8 ratio in bronchoalveolar lavage fluid was significantly increased in cyclosporine-resistant cases compared to alive ones. Suda et al also described that the ratio of CD4/8 lymphocytes was higher in acute/subacute intestitial lung disease than chronic intestitial lung disease in clinically amyopathic dermatomyositis, but the difference was not statistically significant (Suda et al, 2006). Increased CD4/8 ratio in bronchoalveolar lavage fluid suggests that CD8 + T cells may not be major pulmonary inflammatory cells causing lung injury in PM-DM.…”
Section: Bronchoalveolar Lavage Analysismentioning
confidence: 95%
“…NSIP observed in PM-DM patients means the better survival compared with patients with idiopathic pulmonary fibrosis (Douglas et al, 2001) and mortality is similar to that seen in idiopathic NSIP (Tansey et al, 2004). In intestitial lung disease with clinically amyopathic dermatomyositis, although the most common finding is NSIP (Suda et al, 2006), the intestitial lung disease often takes an aggressive course even when the radiological and histological features are consistent with NSIP (Miyazaki et al, 2005). Tiju et al reported that digital infarcts with microangiopathy may be a useful indicator for early intervention in intestitial lung disease associated with DM (Tjiu et al, 2004).…”
Section: Prognostic Factors Associated With Poor Outcome Of Interstitmentioning
confidence: 99%
“…Patients with CADM have a greater risk of developing ILD, especially prone to rapidly progressive lung disease corresponding to DAD [111,112]. Anti-melanoma differentiation-associated gene 5 (MDA5) antibodies (also referred to as anti-CADM-140 antibodies) were identified in the serum from patients with CADM by firstly immunoprecipitation assays [113].…”
Section: Amyopathic Dermatomyositismentioning
confidence: 99%